A study on the optimal line integrated design analysis system - Kim, Taesung; Lee, Hyunsoo; Hong, Heedong (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper is a study on a system that standardizes processes based on smart virtual production technology strategy for manufacturing line design and development, and integrates new or existing resources and systems into one consistent and structured framework.Methods/Statistical analysis: In this paper, we standardize the process based on the digital virtual production technology strategy for manufacturing line design and development. A system that integrates new or existing resources and systems into a single, unified framework. Through this system, various events participating in the development of the manufacturing line can receive standardized work progress and communication in one consistent system. In addition, we standardized and library the scattered data to minimize the loss of data management.Findings: Users across a wide range of areas can quickly and easily perform line development from line planning to design, setup and optimization based on standardized processes and an intuitive user experience. By providing analysis results in conjunction with heterogeneous analysis engines, you can perform solution-independent business processes. The effectiveness of the proposed system was verified by applying the proposed system to the actual new and expansion manufacturing line and redesign line in the company and performing line development work.Improvements/Applications: Through this study, it is expected that the actual field data of MES (Manufacturing Execution System) and the information of planning system such as ERP (Enterprise Resource Planning) can be linked to the integrated decision support system of engineering solution.Â Â